Pola Interaksi dan Sirkulasi Ruang Pengunjung Museum Studi Kasus Museum Ranggawarsita Semarang - Ivan Valentino; Satriya Wahyu Firmandhani (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
Research aims to identify patterns of interaction in the delivery of information and circulation flow in the Ranggawarsita Semarang museum. Techniques for conveying information from collectibles have a very close correlation with the circulation of space in a museum. The Ranggawarsita Museum, Central Java, was a case study by observing directly at the museum location and collecting data using a questionnaire method. This questionnaire method is useful for knowing the visitor's response to this problem of interaction patterns and circulation flow. The discussion will focus on identification through observation by comparing it with standard spatial theories assisted by the results of the questionnaire in determining what patterns are formed from the information conveyed by the museum to museum’s visitors. By identifying the techniques for conveying information and the circulation flow of visitors to the Ranggawarsita museum, in addition to obtaining patterns of interaction, they are also able to identify the problems that exist in it and the roles related to the aspects concerned.